Implementation of Information Technology in the Development of Islamic Educational Institutions - Mawarny, Endah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The study aims to describe digitalization at MAN Luwu .This research is a qualitative research using a Managerial approach. The data source is primary data sourced from the Principal and Islamic Religious Education Teachers, Students. While secondary data is taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, data analysis, data interpretation, and instruments in collecting data are observation, interviews, and documentation.The results of the study show that the Education Management Information System (SIMDIK) of the Luwu State Islamic Senior High School consists of services for educators and education personnel by empowering the SIMPATIKA application (Educator and Education Personnel Information System of the Ministry of Religion), e-learning applications, both for teachers and students and web-based applications in accepting new students. Implementationdigital-based madrasah managementThe State Senior High School of Luwu focuses on students with the implementation of digital-based learning. It has a lot of applications and requires seriousness from teachers to be able to develop various applications for learning.in accordance. The digital-based learning evaluation system can be implemented or applied through the Digital RDM (Digital Madrasah Report) application. In the implementation of the use of the Education Management Information System (SIMDIK) there are driving factors and inhibiting factors. The driving factors include the existence of the SIMPATIKA information system which carries out data collection bothstudentas well as educators, education personnel (PTK) and e-learning